Impact of Exchange Rate Volatility on Economic Growth: Evidence from Selected OIC Countries - Alam, Aftab; Bacha, Obiyathulla Ismath; Ibrahim, Mansor H (Asian Academy of Management Journal of Accounting and Finance, 2025)
This study examines how exchange rate volatility (ERV) impacts economic growth in 18 Organisation of Islamic Cooperation (OIC) countries (1985–2022) through direct and indirect channels. Using the CS-ARDL model and Dumitrescu-Hurlin causality tests, we analyse ERV’s effects via inflation, FDI, external debt, trade, and financial development. Results show ERV significantly reduces long-term growth directly via uncertainty and indirectly through key determinants. While FDI, trade, and financial development support growth, inflation and external debt amplify ERV’s negative effects. Robustness checks (CCEMG and AMG estimators) confirm these findings. OIC policymakers should implement OIC-wide local-currency swap networks and Sharia-compliant hedging instruments (wa?d-based forwards, mur?ba?ah swaps), strengthen Islamic money markets, and adopt inflation control with local-currency trade invoicing to mitigate ERV while boosting growth.